Method for depolymerizing polyethylene terephthalate by glycolysis

JP2024521055A5Active Publication Date: 2025-04-15AQUAFIL SPA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023570039
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-05-17
Filing Date
2022-05-16
Publication Date
2025-04-15
Estimated Expiration
2042-05-16

AI Technical Summary

Technical Problem

Current PET depolymerization methods using metal catalysts face challenges such as high environmental impact, difficulty in removing catalysts from the monomer, high production costs, and limited applicability to PET waste with significant contaminants, particularly from post-consumer carpets.

Method used

The use of calcium acetate, magnesium acetate, or aluminum acetate as catalysts, which are derived from readily available and inexpensive alkaline earth metals, allowing for in situ preparation and efficient depolymerization of PET-containing materials, including those with high contaminant levels, by glycolysis.

Benefits of technology

These catalysts achieve high depolymerization rates and yields comparable to or exceeding traditional metal catalysts, enabling the recycling of a wider range of PET waste, including post-consumer carpets, with reduced environmental impact and lower production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The present invention relates to a process for depolymerization of a material comprising polyethylene terephthalate (PET) by glycolysis with ethylene glycol (EG), comprising reacting the material comprising PET with EG in the presence of at least one catalyst to obtain glycollysis products comprising bis(2-hydroxyethyl) terephthalate (BHET) and / or its oligomers, the catalyst comprising an acetate salt of a metal selected from calcium, magnesium, aluminum, and mixtures thereof. The catalyst can be prepared by in situ reaction of acetic acid with a compound comprising the metal.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a process for the depolymerization of polyethylene terephthalate by glycolysis, in particular, said process using a catalyst that has reduced environmental impact and can be prepared from readily available raw materials. [Background technology]

[0002] Polyethylene terephthalate (PET) is a semi-crystalline thermoplastic polyester with high strength and high transparency. PET is obtained by the esterification reaction of terephthalic acid (TPA) with ethylene glycol (EG) or the transesterification reaction of dimethyl terephthalate (DMT) with EG. Due to its physical and chemical properties, PET has many applications. Specifically, PET is used for the manufacture of textile fibers and carpets (fiber grade PET), food containers (e.g., beverage bottles, bottle grade PET), and food packaging films (film grade PET).

[0003] Currently, global PET production amounts to more than 80 million tons per year. In view of the high consumption and non-biodegradability of PET, there is a strong technological need to recycle this material in order to reduce the environmental impact of used products and the consumption of petroleum-derived raw materials for the manufacture of new products.

[0004] The first method of PET waste recycling is by the so-called "mechanical recycling". Mechanical recycling is based on the mechanical separation of the polymer from contaminants and subsequent re-granulation. Specifically, mechanical recycling involves sorting and separation of the PET waste, removal of contaminants, crushing, heat treatment and extrusion into granules. This recycling technology is widely used but limited, as it can only be used to recover PET from bottles, and the contaminant content is relatively low (less than about 10% (w / w)). In addition, the presence of dyes and other additives in the PET waste, as well as the need for re-granulation to be able to reintroduce it into the industrial production cycle, results in a recycled polymer of lower quality than the polymer obtained from virgin raw materials. Mechanical recycling is further accompanied by the accumulation of the above-mentioned contaminants in the polymer, resulting in a deterioration of the polymer quality obtained each time it is recycled.

[0005] The second method of PET waste recycling is the so-called "chemical recycling". Chemical recycling is based on the chemical conversion (depolymerization) of PET polymer chains into their starting monomers or oligomers by solvolysis. The PET depolymerization products can be easily purified from contaminants and then used in new polymerization processes, thus overcoming the drawbacks associated with mechanical recycling methods. As chemical recycling makes it possible to obtain original raw materials from the treatment of PET waste, this technology has the additional advantage of meeting the criteria that underpin the concepts of circular economy and sustainable development.

[0006] The PET depolymerization reaction can be carried out in several ways: Hydrolysis (acidic, alkaline or neutral) to produce the monomers EG and TPA. Methanolysis to produce DMT, which is then converted to PET by transesterification with EG. Glycolysis, e.g., degradation of polymer chains by EG to produce bis-2-hydroxyethyl terephthalate (BHET).

[0007] Currently, depolymerization by glycolysis with EG is considered to be the most advantageous recycling technology with the greatest potential for development, since it leads to a product (the compound BHET) that can be directly used as a monomer in the synthesis of PET or other widely used polymers (e.g., unsaturated polyester resins for polyurethane production).

[0008] Depolymerization of PET by glycolysis with EG is generally carried out at temperatures ranging from 180°C to 250°C and at atmospheric pressure, usually in the presence of a catalyst. During depolymerization, the polymer chains are transformed by solvolytic scission of the polymer chains, theoretically resulting in monomers (BHET) through complete depolymerization or monomers along with oligomers through partial depolymerization.

[0009] A schematic diagram of the reaction for the depolymerization method of PET using EG is shown in Diagram 1 below. [ka]

[0010] BHET can be used as a monomer to produce various grades of PET (bottle grade, fiber grade, and film grade) with characteristics and properties completely equivalent to those of PET obtained from virgin raw materials. The polymerization reaction leading to the formation of PET from BHET is shown in Diagram 2. [ka]

[0011] Polymerization of BHET liberates one mole of EG, which can be recycled, for example, in a depolymerization process.

[0012] The depolymerization reaction can be carried out in the presence or absence of a catalyst, however, non-catalyzed depolymerization is an economically unfeasible process due to the low conversion yield of PET to BHET and significantly longer reaction times compared to catalytic glycololysis.

[0013] The most commonly used catalysts for PET depolymerization are mainly based on metal salts, specifically Zn, Ti, Pb, Mn, and Na salts. The salts of these metals are usually acetates, carbonates, bicarbonates, and hydrochlorides. In industrial processes, zinc acetate is by far the most widely used catalyst due to its high efficiency in terms of the rate and yield of the depolymerization reaction.

[0014] At the end of the depolymerization, the metals introduced with the catalyst must be removed from the monomer before being used to produce further polymer, in order to prevent interference with the quality of the final product and to avoid accumulation in the polymer during subsequent recycling cycles.

[0015] Catalytic depolymerization processes using metal salts as catalysts are described, for example, in EP 0 723 951 A1 and WO 2017 / 087752 A1.

[0016] EP 0723951 A1 describes a method for preparing high purity BHET by depolymerizing PET from recycled post-consumer or industrial waste. Preferably, the depolymerization is catalyzed by catalysts based on Zn acetate, La acetate, and Ce acetate, or titanium butoxide (Ti(OBu)4). In the only example of the process implementation, zinc acetate is used as catalyst in an amount of about 2.2 mmol / kg (PET+EG). EP 0723951 A1 further mentions calcium acetate and other compounds among the catalysts tested, showing that calcium acetate is less effective compared to zinc acetate.

[0017] WO 2017 / 087752 A1 describes a method for chemical recycling of PET in which the depolymerization reaction is assisted by microwaves. The reaction mixture comprises a catalyst system comprising a catalyst and a microwave absorber. The catalyst is preferably a zinc salt, specifically zinc acetate. Alternative catalysts include magnesium acetate.

[0018] Metal catalysts for PET depolymerization currently used in the state of the art have several drawbacks: Firstly, the most effective catalysts are based on transition and heavy metals (e.g. Zn, Ti, Pb), i.e. elements with high environmental impact, which are rather difficult to remove from the BHET monomer at the end of the depolymerization.

[0019] Secondly, since the catalyst is used in relatively large amounts (the catalyst / PET ratio in the reaction mixture can be in the range of 4%-6% (w / w) depending on the type of catalyst and the reaction conditions), it is crucial in industrial plants to ensure that a large amount of catalyst is always available in order to guarantee the continuity of the depolymerization process. This means that the plant is provided with adequate storage space for the catalyst, which very often must also be stored under controlled humidity and temperature conditions to prevent degradation (e.g., alkali and alkaline earth metal acetates are hygroscopic).

[0020] Third, since the catalysts are synthetic compounds, their production costs are relatively high, significantly affecting the final cost of the resulting BHET.

[0021] In view of the aforementioned drawbacks, it is clear that the state of the art clearly requires a catalytic depolymerization process using an alternative catalyst with respect to the known art processes. In particular, the catalyst should have a low environmental impact and be readily and cheaply available.

[0022] A further drawback of PET recycling methods is the limited types of waste that can be depolymerized. Currently, PET waste recovered by depolymerization comes almost exclusively from the separate collection of plastic containers, especially bottles. Other types of waste, especially PET fibers from spinning processes or post-consumer carpet collection, remain largely unused and end up in landfills due to the high levels of contaminants they contain.

[0023] Carpets containing PET consist of a multi-layer structure containing different kinds of materials, for example polymeric and non-polymeric materials, and there are various inorganic substances used as additives. Specifically, in carpets, polyester is used to create the fiber parts visible from the outside, the underlying support fabric or mesh to which said fiber parts are bonded (so-called primary backing), or the backing of the carpet in contact with the support surface (so-called secondary backing). Intermediate layers of adhesives or reinforcing materials, such as rubber latex and filler materials (e.g. calcium and magnesium salts, aluminum compounds), can be placed between these layers. At the end of their life cycle, carpets containing PET are generally shredded and separated of the contaminant fraction, resulting in a fibrous material with a cotton-like appearance (so-called fluff). The fluff contains PET together with a relatively large amount of contaminants (up to about 20% by weight), the most abundant of which are calcium and / or magnesium carbonate, dolomite minerals, aluminosilicates, and aluminum trihydroxide.

[0024] The particular structure and chemical composition of carpets, together with contaminants adsorbed during use (e.g. adhesives), make the recovery of the PET contained in them rather complicated and economically unfeasible. However, PET waste from carpets remains a very interesting source of material for recycling due to its availability in large quantities. It is therefore desirable to develop a depolymerization method that can also effectively use this type of material. Summary of the Invention [Problem to be solved by the invention]

[0025] In view of the above-mentioned state of the art, the Applicant was therefore faced with the problem of providing a method for the depolymerization of materials, including PET, which overcomes the above-mentioned drawbacks of the known art. In particular, the Applicant was faced with the problem of providing a depolymerization method using a catalyst that has a reduced environmental impact and an efficiency similar to or even superior to known catalysts. In addition, the catalyst must be readily available or easily preparable from raw materials having these characteristics.

[0026] The applicant further addressed the problem of providing a depolymerization process that can provide PET-containing materials derived from various types of waste and processing scrap, including PET-containing materials derived from waste containing significant amounts of contaminants, such as waste from post-consumer carpet recycling. [Means for solving the problem]

[0027] It has now been found that these and other objects, further exemplified in the following description, can be achieved by a method for the depolymerization of materials, including PET, using calcium acetate, magnesium acetate or aluminum acetate as catalyst. It has been found that these salts have an efficiency similar to, and sometimes even higher than, the most efficient catalysts known in the state of the art, such as zinc acetate, while having a reduced environmental impact, since the metal components are not composed of heavy or transition metals, but of alkaline earth metals (Ca and Mg) and amphoteric metals (Al). Moreover, these salts are readily available, relatively cheap and can be easily removed from the BHET obtained at the end of the depolymerization, even by a simple washing with water.

[0028] In some cases (e.g. calcium acetate), the catalysts according to the invention, even at low weight concentrations, show higher reaction rates than known catalysts, making it possible to complete the depolymerization in a shorter time than known processes, which offers the advantage that smaller reactor volumes can be used for the same production capacity than those required in state-of-the-art processes.

[0029] Applicant has also surprisingly found that depolymerization catalysts can be generated in situ in a reaction mixture of acetic acid and a compound containing a metal counterion, such as an oxide, hydroxide, carbonate, or bicarbonate of the aforementioned metals. By appropriately adding acetic acid and a metal-containing compound to the reaction mixture, it was possible to generate acetates of metals capable of catalyzing the depolymerization reaction with efficiency entirely similar to that of the same compounds prepared ex situ and added to the reaction mixture, both in terms of reaction rate and conversion yield of PET to BHET.

[0030] The in situ generation of catalysts from readily available, low-cost, low-environmental impact reagents makes it possible to overcome the disadvantages associated with the supply of catalysts of the known techniques mentioned above.

[0031] Advantageously, it has also been observed that catalysts can be prepared in situ by using metal compounds present as contaminants in the PET-containing material fed to the depolymerization, such as calcium carbonate, a mixture of calcium and magnesium carbonates, or aluminum hydroxide, which are commonly present in materials derived from post-consumer carpet waste. This allows for the utilization of a wide range of PET waste, particularly that which is currently mainly disposed of in landfills, for the production of BHET, such as post-consumer carpet waste.

[0032] Additionally, the in situ catalyst preparation method described herein is not limited to only Ca, Mg, and Al acetates, in fact, the method can be advantageously utilized in the depolymerization of PET-containing materials by glycolysis in the presence of any metal acetate salt capable of effectively acting as a depolymerization catalyst, such as catalysts known in the art, such as zinc acetate, lead acetate, iron acetate, manganese acetate, and antimony acetate.

[0033] Thus, according to a first aspect, the present invention relates to a process for the depolymerization of a material comprising polyethylene terephthalate (PET) by glycolysis with monoethylene glycol (EG), comprising reacting the material comprising PET with EG in the presence of at least one catalyst to obtain a glycolized product comprising bis(2-hydroxyethyl) terephthalate (BHET) and / or its oligomers, said catalyst comprising an acetate of a metal selected from calcium, magnesium, aluminium and mixtures thereof.

[0034] According to a second aspect, the present invention relates to a process for the depolymerization of a material comprising polyethylene terephthalate (PET) by glycolysis with ethylene glycol (EG), comprising reacting PET with EG in the presence of at least one catalyst comprising an acetate of a metal to obtain glycolysis products comprising bis(2-hydroxyethyl) terephthalate (BHET) and / or its oligomers, said catalyst being obtained in situ by reaction of acetic acid with a compound comprising said metal. [Brief description of the drawings]

[0035] [Figure 1] FIG. 2 is a graph showing the time-dependent tendency of the total yield of the depolymerization reaction in Examples 1 to 3. [Diagram 2] FIG. 1 shows the time-dependent trend of the total yield of the depolymerization reaction in Examples 4 and 5. [Diagram 3] FIG. 1 shows the time-dependent trend of the total yield of the depolymerization reaction in Examples 6 and 7. [Figure 4] FIG. 1 shows the time-dependent trend of the total yield of the depolymerization reaction in Example 8. [Diagram 5] FIG. 1 is a graph showing the time-dependent tendency of the total yield of the depolymerization reaction in Examples 9 and 10. [Figure 6] FIG. 13 shows the time-dependent trend of the total yield of the depolymerization reaction of Example 12 compared to Example 13. [Figure 7]FIG. 13 shows the time-dependent trend of the total yield of the depolymerization reaction in Example 14. [Figure 8] FIG. 14 shows the time-dependent trend of the total yield of the depolymerization reaction of Example 15 compared to Example 3. [Figure 9] FIG. 1 shows the time-dependent trend of the total yield of the depolymerization reaction of Example 16 compared to Example 5. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0036] Generally, the PET-containing material fed to the depolymerization process according to the invention may be any material containing PET in an amount of preferably 60% by weight or more, more preferably 70% by weight or more, even more preferably 80% by weight or more, said material may contain contaminants, i.e. compounds other than PET, in an amount of 40% by weight or less, preferably 30% by weight or less, even more preferably 20% by weight or less.

[0037] Examples of contaminants commonly present in PET-containing materials from recovered waste are dyes, polyolefins (e.g., polyethylene or polypropylene), rubber latex, polyamides, polyvinyl alcohol (EVOH), polyvinyl acetate (EVA), UV absorbers; fillers (e.g., calcium carbonate, magnesium carbonate, aluminum hydroxide, titanium dioxide, carbon black, silica), metal particles (e.g., aluminum), and other contaminants resulting from the use of the article.

[0038] Preferably, the PET-comprising material comprises post-consumer PET waste and / or post-industrial PET waste, which may come from a wide variety of products, for example: · transparent and / or coloured PET bottles for food products (e.g. water, soft drinks, etc.); · multilayer PET articles in which PET layers are combined with layers of other polymeric or metallic materials, usually for the food industry; · Articles containing PET fibres such as textiles and carpets.

[0039] In particularly preferred embodiments, the depolymerized material comprises post-consumer waste and / or post-industrial scrap comprising PET, preferably post-consumer carpet waste comprising PET.

[0040] The PET-containing material can be fed to the depolymerization process in the form of granules, flakes, fibers, or fluff.

[0041] The depolymerization catalyst is present in the reaction mixture in an amount effective to depolymerize the PET present in the reaction mixture. Preferably, the catalyst is present in the reaction mixture in an amount in the range of 0.1% to 5% by weight, more preferably in the range of 0.4% to 2.0% by weight, based on the weight of PET contained in the material to be depolymerized.

[0042] Preferably, the catalyst is present in the reaction mixture at a ratio of greater than 5 mmol of catalyst, more preferably greater than 15 mmol of catalyst, even more preferably greater than 20 mmol of catalyst, for example in the range of 20 to 50 mmol of catalyst, per kg (PET+EG), where "PET+EG" is the total weight of EG and PET present in the PET-containing material.

[0043] As mentioned above, the catalyst can be prepared in situ and added to the reaction mixture as such, or the catalyst can be prepared by the in situ reaction of acetic acid and a compound containing at least one metal capable of producing an acetate salt of the metal with the acetic acid.

[0044] In this specification, the expression "metal acetate" also includes mixed salts, i.e. salts of metals in which, in addition to the acetate anion (hereinafter also referred to as "Ac"), one or more counterions other than acetate are present. An example of a mixed salt is calcium bicarbonate acetate (hereinafter also referred to as Ca(HCO3)Ac), which can be obtained by reacting acetic acid with calcium carbonate in the appropriate stoichiometric ratio.

[0045] Preferably, the metal-containing compound is selected from oxides, hydroxides, carbonates, bicarbonates, chlorides, and mixtures thereof.

[0046] Preferably, the metal containing compound is selected from calcium carbonate, calcium bicarbonate, calcium hydroxide, magnesium carbonate, magnesium bicarbonate, magnesium hydroxide, aluminium hydroxide, aluminium trichloride.

[0047] As mentioned above, when the catalyst is prepared in situ, it may contain acetates other than Ca acetate, Mg acetate, and Al acetate, in such cases, the metal-containing compound comprises at least one metal selected from zinc, iron, manganese, antimony, and mixtures thereof, said compound being in the form of an oxide, hydroxide, carbonate, bicarbonate, or chloride.

[0048] The reagents necessary to generate the in situ catalyst can be added together or separately to the EG or to a mixture containing EG and the PET-containing material.

[0049] In a preferred embodiment, the PET-containing material further comprises a metal-containing compound in a catalytically effective amount, i.e., an amount sufficient to provide an acetate capable of catalyzing the depolymerization reaction upon reaction with acetic acid. If the concentration of the metal-containing compound is not sufficient to provide a catalytically effective amount of metal acetate, then a metal compound can be purposefully added to the reaction mixture.

[0050] Preferably, acetic acid is added to the reaction mixture in an amount in the range of 0.01% to 5% by weight, more preferably in the range of 0.03% to 1.5% by weight, and even more preferably in the range of 0.1% to 1% by weight, based on the PET-containing material.

[0051] Preferably, the metal-containing compound is added to the reaction mixture in an amount in the range of 0.01% to 5% by weight, more preferably in the range of 0.02% to 1.8% by weight, and even more preferably in the range of 0.06% to 1.2% by weight, based on the PET-containing material.

[0052] Preferably, the molar ratio of acetic acid to the metal compound is in the range of 1:1 to 1:10.

[0053] The applicant has noted that the metal acetate formation reaction may compete with the reaction of acetic acid with EG with the formation of the corresponding ethylene glycol monoacetate polyester (EGMA) or ethylene glycol diacetate polyester (EGDA), and thus affect the yield of the acetate-catalyzed formation reaction. However, it has been found that this can be overcome by adding acetic acid and a metal compound to EG, or a mixture of EG and PET, under appropriate conditions. Specifically, it is preferred to first mix acetic acid and a metal compound with a material comprising EG and optionally PET at a relatively low temperature, preferably in the range of 20° C. to 70° C., more preferably 20° C. to 50° C., and even more preferably 20° C. to 40° C., and then to proceed by raising the temperature of the mixture to a temperature selected for the depolymerization reaction. Without referring to any particular theory, at low temperatures, the catalyzed formation reaction is favored over the formation of EGMA esters and EGDA esters, and once the metal acetate is formed, the temperature of the reaction mixture can be raised to the depolymerization temperature without resulting in the formation of EGMA esters and EGDA esters.

[0054] If metal compounds are present in the PET-containing material to be depolymerized, the latter are also added to the EG and acetic acid, preferably at low temperature.

[0055] In particular, in one embodiment, a depolymerization method including in situ catalyst generation comprises: a. mixing acetic acid, a metal-containing compound, and EG at a temperature in the range of 20°C to 70°C, preferably 20°C to 50°C; b. heating the mixture obtained in step a to a temperature in the range of 170°C to 230°C; and c. feeding a material containing PET to the mixture obtained in step b to obtain a glycolysate. Includes.

[0056] The in situ preparation of the catalyst is particularly useful when the PET-containing material further comprises one or more metal compounds that act as precursors for the in situ generation of the catalyst by reaction with acetic acid. In fact, it is possible to determine the metal content of the material and then add acetic acid to the reaction mixture. When metal compounds are present in a relatively large amount in the PET-containing material, it is possible to add enough acetic acid at any one time to convert only a small part of the metal compounds and generate the required amount of catalyst. The remainder of the metal compounds present as contaminants are then removed in the purification step of the glycolysate. This is especially true in the case of recycled PET from recovered carpets (fluff), which usually contains at least 3% to 5% by weight of calcium carbonate and / or aluminum hydroxide.

[0057] In particular, in one embodiment, a method for depolymerization using in situ catalyst generation includes: a. mixing EG, acetic acid, the PET-containing material, and the metal-containing compound at a temperature in the range of 20°C to 70°C, preferably 20°C to 50°C; b. heating the mixture obtained in step a to a temperature in the range of 170°C to 230°C to react and obtain glycol decomposition products; Includes.

[0058] Preferably, the glycolysis reaction is carried out at a temperature in the range of 170° C. to 230° C., more preferably in the range of 190° C. to 210° C. Heating of the reaction mixture is not performed by microwave irradiation.

[0059] In certain embodiments, when the catalyst comprises magnesium acetate, heating of the reaction mixture is not performed by microwave irradiation.

[0060] In the glycolysis reaction, EG is preferably used in a weight ratio of EG:PETm in the range of 1:1 to 8:1, more preferably in the range of 1:1 to 4:1, and even more preferably in the range of 1:1 to 2:1, where PETm denotes a material containing PET.

[0061] The duration of the glycolysis reaction can vary over a wide range depending on the reaction conditions such as temperature, agitation, and type of reactor. Usually, the reaction time is from 1 hour to 6 hours, preferably from 1.5 hours to 4 hours. The reaction can be carried out in a batch or continuous process. The reaction pressure is usually atmospheric, but reduced or increased pressure may be used.

[0062] The glycolysis reaction results in the production of a glycolysis product comprising BHET and / or its oligomers. At the end of the depolymerization, the glycolysis product typically also contains a residual fraction of material comprising unreacted PET and other depolymerization products (e.g., water, EG insoluble contaminants, etc.).

[0063] The BHET and / or its oligomers can be separated from the glycol degradation products and purified using suitable techniques known in the art, such as distillation, filtration, and crystallization.

[0064] The BHET and / or its oligomers obtained by the methods described herein can be used as feedstocks in new processes for the production of polyester polymers and copolymers, for example, they can be polymerized to produce PET, either from recycled BHET alone or in combination with BHET made from virgin feedstocks.

[0065] The processes described herein can be carried out using equipment and devices known in the art for the production of polymers, particularly polyesters.

[0066] Advantageously, the depolymerization reaction can be carried out in an acid-resistant stainless steel reactor equipped with suitable inlets for the addition of liquid acetic acid and solid compounds for in situ catalyst generation. The reactor can be equipped with heating and mixing means for heating the reaction mixture to the desired temperature and maintaining agitation. EXAMPLES

[0067] The following examples are provided solely for the purpose of illustrating the present invention and should not be considered as limiting the scope of protection defined by the appended claims.

[0068] In the examples, reference is made to the accompanying Figures 1 to 7, which illustrate the time-dependent trends of the total yield of the glycolysis reaction for Examples 1 to 14.

[0069] Working Example 1. Depolymerization test The efficiency of the method according to the present invention was verified by a series of catalytic depolymerization tests of different types of PET-containing waste. The depolymerization tests were carried out as follows.

[0070] The glycolysis reaction was carried out in a 1 liter round bottom Pyrex glass reaction flask. The flask is heated by a heating mantle (isomantle). The reaction flask is equipped with four necks with the following functions: A thermocouple is inserted into the first port to detect the temperature of the liquid mixture during the reaction, and the temperature set point can be set digitally by a heating mantle. A reflux condenser is inserted into the second port to condense the vapors evolved during the reaction using a continuously supplied stream of cold water. The remaining two ports are used to feed materials including monoethylene glycol (EG) and PET, and these two ports are kept closed by two ground glass stoppers during the depolymerization reaction.

[0071] The reaction mixture was kept stirred by a magnetic stirrer using a PTFE magnetic stirring rod, the rotation speed of which can be digitally set by an isomantle. The reaction temperature and rotation speed were set at 195° C. and 1400 rpm, respectively.

[0072] EG and the catalyst (if prepared in lab) are initially charged into the reaction flask. The mixture, maintained under stirring, is then heated to reaction temperature while the resulting vapors are recondensed by a bubble condenser. Once the glycol and catalyst mixture has reached reaction temperature, a PET-containing material (hereafter also simply referred to as "PET") preheated to 110°C is introduced into the flask.

[0073] The moment when PET begins to be charged to the reaction flask is designated "time zero" (t0) at the start of the reaction. Starting at t0, samples of the glycolysis fluid are taken at regular intervals using a glass Pasteur pipette, then transferred to a vial cooled with ice-water to stop the reaction progress, and then analyzed by HPLC to determine the content of BHET and its oligomers.

[0074] The time at which complete dissolution of the PET in the glycol is observed is also noted.

[0075] At the end of the glycolysis, the contents of the flask are removed and the liquid is subjected to end-of-process HPLC analysis.

[0076] 2. Examples 1 to 3 (Comparative) Catalyst: Zinc acetate (ZnAc2) Following the procedure described in point 1, the depolymerization of granulated PET was carried out in the presence of zinc acetate, adding catalyst at different concentrations. The PET used was in practically pure form (purity about 100%). The composition of the reaction mixture is shown in Tables 1 to 3 together with the analytical results of the reaction liquid taken at different reaction times.

[0077] The weight ratio of EG / PET and the weight ratio of catalyst / PET represent the weight ratio of EG and the weight ratio of catalyst to the material containing PET, respectively.

[0078] The parameters "BHET Yield", "Dimer Yield" (of BHET) and "Total Yield" represent the ratio of the amount of BHET, the amount of BHT dimer and the amount of total "BHET+dimer" to the weight of the material including PET, respectively, expressed as mole / mole (%).

[0079] [Table 1]

[0080] [Table 2]

[0081] [Table 3]

[0082] FIG. 1 shows the time-dependent trend of the total yield of the depolymerization reaction.

[0083] 3. Examples 4 and 5 Catalyst: Calcium acetate (CaAc2) Following the method described in point 1, granular PET (100% purity) was depolymerized in the presence of calcium acetate added at 1% and 3% by weight of the input PET.

[0084] The composition of the reaction mixture is shown in Tables 4 and 5 together with the analytical results of the reaction solution sampled at different reaction times.

[0085] [Table 4]

[0086] [Table 5]

[0087] FIG. 2 shows the time-dependent trend of the total yield of the depolymerization reaction.

[0088] Comparison of the results of Examples 1-3 with those of Examples 4-5 shows that the CaAc2 catalyst has similar efficiency to ZnAc2 and a faster depolymerization reaction rate than ZnAc2 for the same weight of catalyst.

[0089] 4. Examples 6 to 7 Since the physical form of the PET-containing material can also affect the extent of the depolymerization reaction, the procedure described in step 1 was carried out by feeding a PET-containing waste consisting of spinning waste (purity about 97.5%) and using ZnAc2 and CaAc2 as catalysts.

[0090] The composition of the reaction mixture is shown in Tables 6 to 7 together with the analytical results of the reaction solution sampled at different reaction times.

[0091] [Table 6]

[0092] [Table 7]

[0093] FIG. 3 shows the time-dependent trends of the total yield of the depolymerization reactions of Examples 6 and 7.

[0094] These examples compare two different weight loadings, which are found to correspond to the same molar loading (approximately 5.5 mmol of catalyst).

[0095] A comparison of the graphs in Figure 3 shows that CaAc2 is a depolymerization catalyst that achieves results almost similar to those of conventional ZnAc2, even at low weight concentrations. The reaction in the presence of CaAc2 is completed faster than that with ZnAc2.

[0096] 5. Examples 8 to 10 Catalyst: Calcium acetate (CaAc2) The efficiency of CaAc2 catalyst was tested in the depolymerization reaction of PET waste from carpet recycling (fluff). The fluff used had a PET content of 80 wt%.

[0097] The process described in point 1 was carried out by feeding fluff to the reaction mixture containing CaAc2 as catalyst.

[0098] In the fluff feeding test, at the end of the glycolysis reaction, the reaction mixture at 195°C still had a fraction of suspended solids with a tan appearance, which was removed by hot filtration of the reaction mixture (at about 190°C). The insoluble residue separated by filtration, amounting to about 10%-15% of the weight of the input fluff, was analyzed by DSC, TGA, and FT-IR. The analysis revealed the presence of a mixture of polypropylene, adhesives, and other inorganic materials, including calcium carbonate.

[0099] The composition of the reaction mixture is shown in Tables 8 to 10 together with the analytical results of the reaction mixture sampled at different reaction times.

[0100] [Table 8]

[0101] [Table 9]

[0102] [Table 10]

[0103] FIG. 4 shows the time-dependent trend of the total yield of the depolymerization reaction in Example 8, and FIG. 5 shows the time-dependent trend of the total yield of the reactions in Examples 9 and 10.

[0104] Examples 9 and 10 show that even when operating at relatively low CaAc2 catalyst concentrations and EG / PET ratios, similar PET conversion yields to BHET and oligomers are obtained at higher EG / PET ratios as catalysts used in prior art glycolysis processes such as ZnAc2.

[0105] 6. Examples 11-12 Catalyst: Acetic acid and in situ generated calcium bicarbonate acetate (Ca(HCO3)Ac) The following depolymerization tests were carried out according to the procedure described in point 1. In Example 11 (comparison), depolymerization tests were carried out with PET in the form of fibers with virtually no contamination (purity about 97.5%). To test its possible effect as a depolymerization catalyst, only acetic acid was added to the reaction mixture. Acetic acid was added to EG at 30° C., and then the mixture was heated to 195° C. and maintained under reflux. At this temperature, PET fibers were added. After 3 hours of reaction, no dissolution of the fibers was observed and HPLC analysis of the reaction mixture liquid did not detect the presence of BHET.

[0106] Example 12 was carried out under the same conditions as Example 11, except that equimolar amounts of CaCO3 and acetic acid were added to EG at 30°C. The mixture was then heated to 195°C, which was maintained under reflux, and PET fibers were added. The reaction was continued until the fibers were completely dissolved. Thus, the data shown in Table 11 demonstrates that an active equivalent amount of catalyst Ca(HCO3)Ac was produced in the reaction mixture at a concentration of 2.66 wt% relative to the weight of the PET fibers.

[0107] [Table 11]

[0108] FIG. 6 shows the time-dependent trend of the total yield of the depolymerization reaction of Example 12 compared to Example 13.

[0109] 7. Example 13 Catalyst: Acetic acid and in situ generated calcium bicarbonate acetate (Ca(HCO3)Ac) Example 13 was carried out under the same conditions as Example 12, except that acetic acid and PET fluff were added to EG at 30° C., and CaCO3 contained in PET fluff (80% purity) was used. The CaCO3 content in the fluff was about 5% by weight based on the weight of the fluff.

[0110] The composition of the reaction mixture is shown in Table 12 together with the analytical results of the reaction mixture taken at different reaction times.

[0111] [Table 12]

[0112] Figure 6 shows the time-dependent trend of the total yield of the depolymerization reaction in Example 13. The results indicate that the PET glycolysis process in Example 13 proceeds to a similar extent as in Example 12, confirming that it is possible to prepare effective depolymerization catalysts in situ by utilizing metal compounds present as contaminants in recycled PET-containing materials.

[0113] 8. Example 14 Catalyst: Magnesium acetate (MgAc2) According to the method described in point 1, granular PET (100% purity) was depolymerized with magnesium acetate added at 0.45 wt. % MgAc2 relative to the weight of the input PET.

[0114] The composition of the reaction mixture is shown in Table 13 together with the analytical results of the reaction mixture taken at different reaction times.

[0115] [Table 13]

[0116] Figure 7 shows the time-dependent trend of the total yield of the depolymerization reaction of Example 14. The results show that magnesium acetate is also an effective catalyst in PET depolymerization.

[0117] 9. Examples 15 to 18 Other catalysts produced in situ Examples 15 to 18 were carried out under the same conditions as Example 12, In Example 15, acetic acid and zinc carbonate in a molar ratio of 2:1; In Example 16, acetic acid and calcium oxide in a molar ratio of 2:1; In Example 17, acetic acid and magnesium hydroxide in a molar ratio of 2:1; In Example 18, a 3:1 molar ratio of acetic acid and aluminum hydroxide was used. was added to EG at 30°C.

[0118] In each case the mixture was then heated to 195° C., maintained under reflux, and the PET granules were added.

[0119] The composition of the reaction mixture is shown in Tables 14 to 17 together with the analytical results of the reaction mixture taken at different reaction times.

[0120] [Table 14]

[0121] [Table 15]

[0122] [Table 16]

[0123] [Table 17]

[0124] Figures 8 and 9 show the time-dependent trends of the total yield of the depolymerization reactions of Examples 15 and 16 compared to Examples 3 and 5, respectively, where the same catalysts were prepared in situ and then added to the reaction mixture. The results show that the in situ generated catalysts are as effective as those produced in situ.

[0125] 10. Example 19-Example 20 Recovery of BHET by evaporation and crystallization of EG Using the same methods as in Examples 12 and 13, respectively, Examples 19 and 20 focused on separating the BHET and dimer to obtain materials that could be polymerized into PET.

[0126] In this first step, the glycolysis residue was filtered to separate unconverted PET and other impurities from the glycolysis material. A portion of the glycol in the filtered product is evaporated by flash evaporation under vacuum.

[0127] At this point, a large excess of water (four times the weight of glycol) was added to precipitate the product, which was then filtered again, washed with water, and finally dried.

[0128] The resulting material was then analyzed by HPLC, FT-IR, DSC, and NMR and was confirmed to be BHET and its dimer.

[0129] As shown in Table 18, the properties of the isolated product (COOH and diethylene glycol (DEG) content, melting point) match those typically required for the polymerized material.

[0130] [Table 18]

Claims

1. 1. A method for depolymerizing a material comprising polyethylene terephthalate (PET) by glycolysis with ethylene glycol (EG), comprising the steps of: reacting a material comprising PET with EG in the presence of at least one catalyst to obtain glycolyzed products comprising bis(2-hydroxyethyl) terephthalate (BHET) and / or oligomers thereof; wherein the catalyst comprises an acetate of a metal selected from calcium, magnesium, aluminum, and mixtures thereof; method.

2. The method of claim 1 , wherein the catalyst is obtained by in situ reaction of acetic acid with a compound containing the metal.

3. 3. The method of claim 2, wherein the metal-containing compound is selected from oxides, hydroxides, carbonates, bicarbonates, chlorides, and mixtures thereof.

4. 3. The method of claim 2, wherein the metal-containing compound is selected from calcium carbonate, calcium bicarbonate, calcium hydroxide, magnesium carbonate, magnesium bicarbonate, magnesium hydroxide, aluminum hydroxide, aluminum trichloride.

5. The method of claim 2 , wherein the PET-containing material comprises a compound that includes the metal.

6. a. mixing acetic acid, a compound containing the metal, and EG at a temperature in the range of 20° C. to 70° C.; b. heating the mixture obtained in step a to a temperature in the range of 170°C to 230°C; and c. Supplying the PET-containing material to the mixture obtained in step b to obtain a glycolysate. The method of claim 2 , comprising:

7. a. mixing EG, acetic acid, and the PET-containing material and the metal-containing compound at a temperature in the range of 20° C. to 70° C.; and b. Heating the mixture obtained in step a to a temperature in the range of 170° C. to 230° C. to cause the reaction to obtain glycol decomposition products. The method of claim 5 , comprising:

8. 10. The method of claim 1, wherein the PET-containing material comprises post-consumer waste and / or post-industrial scrap containing PET.

9. The method of claim 1, wherein the PET-containing material comprises post-consumer carpet waste containing PET.

10. The method of claim 1 , wherein the PET-containing material is in the form of granules, flakes, fibers, or fluff.

11. The method of claim 1 , wherein the weight ratio of EG to PETm (EG:PETm) is 1:1 to 8:1, where PETm refers to the material comprising said PET.

12. 12. The method of any one of claims 1 to 11, wherein the method does not include heating a reaction mixture in the reaction of a material comprising PET with EG in the presence of the at least one catalyst by microwave irradiation when the catalyst comprises magnesium acetate.

13. 1. A method for depolymerizing a material comprising polyethylene terephthalate (PET) by glycolysis with ethylene glycol (EG), comprising the steps of: reacting a material comprising PET with EG in the presence of at least one catalyst comprising a metal acetate to obtain glycol degradation products comprising bis(2-hydroxyethyl) terephthalate (BHET) and / or oligomers thereof; wherein the catalyst is obtained by an in situ reaction between acetic acid and a compound containing the metal; method.

14. The in situ reaction of acetic acid with a compound containing the metal comprises: a. mixing acetic acid, a compound containing the metal, and EG at a temperature in the range of 20° C. to 70° C.; b. heating the mixture obtained in step a to a temperature in the range of 170°C to 230°C; and c. Supplying the PET-containing material to the mixture obtained in step b to obtain the glycolyzed product. The method of claim 13, comprising:

15. The in situ reaction of acetic acid with a compound containing the metal comprises: a. mixing EG, acetic acid, and the PET-containing material, and the metal-containing compound at a temperature in the range of 20° C. to 70° C.; b. Heating the mixture obtained in step a to a temperature in the range of 170° C. to 230° C. to cause the reaction to occur and obtain the glycol decomposition product. The method of claim 13, comprising: